Ensuring Supply Chain Transparency by Deploying Blockchain-Enabled Technology : An Overview With Demonstration - Shamsuzzoha, Ahm; Shahzad, Khuram; Nousiainen, Essi; Ranta, Mikko; Helo, Petri; Govindan, Kannan (John Wiley & Sons, 2025)
It is nowadays quite challenging to manage and control the supply chain concerning transparency, traceability, and zero-trust security. Digital technology such as blockchain has shown promising features to ease the global supply chain for tracking, tracing, and authenticity. This study critically examines the potential of blockchain technology and smart contracts to manage global supply chain sustainability. It also analyzes the inherent opportunities, benefits, and common barriers to deploying blockchain in the supply chain. Moreover, an overview of blockchain technology and its application in the various industries’ supply chain management is illustrated in this study. Furthermore, an application demo related to blockchain in the supply chain is provided within the scope of this study with the view to demonstrating how various transactions in the supply chain are executed with higher authenticity. The study is concluded with several future research propositions and directions that may provide insight into overcoming current challenges and the adoption of blockchain for the supply chain.
Keywords: blockchain; blockchain demo; smart contracts; supply chain management; zero-trust security and transparency; blockchains; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; fi=Tuotantotalous|en=Industrial Management|